EFFICACY OF HERBAL DRUG IN INDUCING ESTRUS IN DELAYED PUBERTAL DEONI HEIFERS - PATIL, A D; MARKANDEYA, N M; BHIKANE, A U (The Indian Journal of Animal Reproduction, 2023)
Herbal therapies are preferred for treatment of anestrus due to their cheap, safe and efficiencywith easy availability. Delayed maturity is the most common reproductive complaint in native descriptheifers. Eighteen Deoni heifers were selected for treatment of delayed maturity with herbal heat inducerpowder on the basis of gynaeco-clinical examinations. 75.00 per cent heifers responded for the treatmentwith ovulatory, intermediate type of estrus and six animals conceived with 1.33 services per conceptionas against nil response in control group. Estimation of haemoglobin, serum protein, serum copper,serum cobalt and serum iron levels revealed significantly higher increase in treatment group. It wasconcluded that herbal therapy can efficiently induce fertile estrus in delayed cases of maturity in deoniheifers.
Keywords: Deoni; Estrus; Herbals; Puberty